Attention Improves During Physical Exercise in Individuals With ADHD - Rassovsky, Yuri; Alfassi, Tali (Frontiers in Psychology, 2019)
The present study examined the effects of physical exercise on attentional processes in individuals diagnosed with Attention Deficit Hyperactivity Disorder (ADHD), compared to healthy controls. Unlike previous studies typically comparing performance on baseline measures with post-exercise performance, this study examined the effects of physical exercise on attention while participants were engaged in a continuous performance task. Fourteen individuals diagnosed with ADHD and 17 controls completed the Conners Continuous Auditory Test of Attention (CATA). All participants completed the test twice, at baseline in a sitting position and while walking on the treadmill. The order of administration was counterbalanced for each group. Results showed a group by activity interaction on several measures of the CATA. Specifically, the ADHD group demonstrated faster reaction times and decreased omission errors in the physical exercise condition compared with resting, and their relatively lower performance on these measures was only evident in the resting condition, attaining scores similar to controls during exercise. These results suggest a possibly hypoactive attentional system in ADHD that could potentially be enhanced by arousal through engagement in physical exercise.